Situation Report: Romania, 29 June 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Trouble in Store for Elena Ceausescu? Rescheduling the 1983 External Debt Increased Diplomatic Involvement in the Middle East The Party's Hunt for More Land Change in the Statutes of Socialist Agricultural Organizations The 1982 Statistical Yearbook